Curcumin encapsulated in PAMAM dendrimers for the therapeutic treatment of ischemic stroke in rats - Justin Stadler; Justin Stadler; Justin Stadler; Lucas G. Garmo; Lucas G. Garmo; Lucas G. Garmo; David Doyle; David Doyle; David Doyle; Chin-I. Cheng; Garrett Richardson; Garrett Richardson; et al. (Frontiers in Cell and Developmental Biology)
IntroductionIschemic stroke is a devastating neurovascular condition that occurs when cerebral tissue fails to receive an adequate supply of oxygen. Despite being a leading cause of death and disability worldwide, therapeutic interventions are currently limited. Polyamidoamine (PAMAM) dendrimers are nanomolecules commonly used in biomedical applications due to their ability to encapsulate small-molecules and improve their pharmacokinetic properties. Curcumin is known to have anti-inflammatory and antioxidant effects yet suffers from poor solubility and bioavailability. The purpose of this study is to investigate the efficacy of curcumin encapsulated in PAMAM dendrimers as a potential therapeutic treatment for ischemic stroke by studying post-stroke lesion size, astrocyte reactivity, and functional recovery in a rat model of cerebral ischemia.MethodsForty-eight male and female Sprague-Dawley rats (280–380 g) underwent either a 90-min middle cerebral artery occlusion (MCAo) or sham surgery before receiving one of four treatments: (1) Hanks’ balanced salt solution (HBSS) control, (2) empty dendrimer control, (3) curcumin control, or (4) curcumin encapsulated in PAMAM dendrimer. Neurobehavioral outcomes were evaluated at 1-, 3-, 5-, and 7-day post-surgery, after which animals were euthanized on day 8 to assess infarct volume and GFAP immunoreactivity.ResultsAnimals that received formulations containing dendrimers (curcumin encapsulated in dendrimers or empty dendrimers) demonstrated significantly lower levels of GFAP immunoreactivity and improved functional recovery, including weight and neurobehavioral scores, compared to the formulations that did not contain dendrimers (curcumin and HBSS control). Additionally, the dendrimer-curcumin treatment group exhibited a significantly improved paw laterality index over the course of the study compared with the other three treatment groups.ConclusionAlthough the post-stroke administration of curcumin encapsulated in PAMAM dendrimers modulates the astrocytic response and promotes functional recovery following ischemic stroke in rats, its therapeutic benefits may be driven by PAMAM dendrimers as the empty dendrimer treatment group also showed significant improvements post-stroke. Further investigation regarding PAMAM dendrimers in treating neuroinflammatory conditions remains warranted.